2019
DOI: 10.1093/auk/ukz016
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and social correlates of natal dispersal in female and male Thorn-tailed Rayadito (Aphrastura spinicauda) in a naturally isolated and fragmented habitat

Abstract: Sex-biased natal dispersal is predicted to be a consequence of differences in the costs and benefits of dispersal perceived by each sex. Although female-biased dispersal has been described for numerous birds in heterogeneous landscapes, studies documenting sex-related differences in the causes and consequences of natal dispersal in fragmented habitats are comparatively scarce. We used capture-mark-recapture data and genetic analyses in a population of Thorntailed Rayadito (Aphrastura spinicauda) from north-cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 63 publications
0
19
0
Order By: Relevance
“…We used multi‐locus genotypes for parentage analyses following the methods described in Botero‐Delgadillo et al. (2019). Analyses were performed in CERVUS version 3.0.7 (Kalinowski et al., 2007).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used multi‐locus genotypes for parentage analyses following the methods described in Botero‐Delgadillo et al. (2019). Analyses were performed in CERVUS version 3.0.7 (Kalinowski et al., 2007).…”
Section: Methodsmentioning
confidence: 99%
“…As described for other members of the family Furnariidae, both sexes contribute to incubation and feeding the young (Espíndola‐Hernández et al., 2017; Moreno et al., 2005, 2007). Genetic polyandry has been confirmed for rayaditos (Botero‐Delgadillo et al., 2019), but rates of EPP have not yet been quantified and described in this species. Furthermore, population differences in EPP rates may occur given marked environmental variation throughout the species’ extensive geographic range (see e.g., Ippi et al., 2011; Quirici et al., 2014).…”
Section: Introductionmentioning
confidence: 95%
“…DNA extraction from blood samples and individual genotyping were carried out according to the protocol described in Botero‐Delgadillo et al. (2019). 250 birds (88 adults and 206 nestlings) were sexed using a chromosome‐linked marker (P2/P8) and genotyped at 12 polymorphic microsatellite loci.…”
Section: Methodsmentioning
confidence: 99%
“…These allelic mismatches were used to calculate the frequency of genotyping errors in CERVUS. As outlined by Botero-Delgadillo et al (2019), paternity was excluded based on the logarithm-of-odds (LOD) score and the critical Delta value (<80%), or whenever there were two or more mismatches between the social male and its putative offspring.…”
Section: Parentage Analysismentioning
confidence: 99%
“…The study population inhabits a temperate forest relict in Bosque Fray Jorge National Park in north‐central Chile, breeding in tree cavities in forest fragments that are surrounded by a semi‐arid landscape (del‐Val et al, 2006 ; Figure 1 ). Although post‐glacial aridisation have caused the study population to experience a long‐term process of isolation since the end of the tertiary (Villagrán et al, 2004 ), it harbors a relatively high level of genetic diversity (observed heterozygosity, H O =0.67) and a moderate level of inbreeding (population mean inbreeding coefficient, F = 0.18), and it has been suggested that, along with historical factors, female‐biased natal dispersal could account for such level of inbreeding (Botero‐Delgadillo et al, 2019 ; Botero‐Delgadillo, Quirici, Poblete, Acevedo, et al, 2020 ; Botero‐Delgadillo, Quirici, Vásquez, et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%